A Rapid Genome-wide MicroRNA Screen Identifies miR-14 as a Modulator of Hedgehog Signaling. - Kim, K.; Vinayagam, A.; Perrimon, N. (Cell reports, 2014)
MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene expression by binding to sequences within the 3' UTR of mRNAs. Because miRNAs bind to short sequences with partial complementarity, target identification is challenging. To complement the existing target prediction algorithms, we devised a systematic "reverse approach" screening platform that allows the empirical prediction of miRNA-target interactions. Using Drosophila cells, we screened the 3' untranslated regions (3' UTRs) of the Hedgehog pathway genes against a genome-wide miRNA library and identified both predicted and many nonpredicted miRNA-target interactions. We demonstrate that miR-14 is essential for maintaining the proper level of Hedgehog signaling activity by regulating its physiological target, hedgehog. Furthermore, elevated levels of miR-14 suppress Hedgehog signaling activity by cotargeting its apparent nonphysiological targets, patched and smoothened. Altogether, our systematic screening platform is a powerful approach to identifying both physiological and apparent nonphysiological targets of miRNAs, which are relevant in both normal and diseased tissues.